Pola Hedonic Treadmill dalam Perilaku Akuntansi - Driana Leniwati; Dita Suci Permatasari (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Purpose: This study aims to analyze the hedonic treadmill pattern in behavioral accounting in the millennial generation of shopee users. This study emphasizes the concept of behavioral accounting that is implemented in social phenomena in economic decision making based on the hedonic treadmill pattern.Method: This study uses a qualitative descriptive method with a case study approach. The data were obtained by conducting interviews with key informants. Data analysis techniques in this study were data reduction, data presentation, and conclusion/verification.Results: The results of the study show that there are four styles in making buying decisions in the millennial generation, namely the director's style, analytic style, conceptual style, and attitude style. In addition, the millennial generation is also driven by hedonic shopping motivation. From the empirical results, it was found that decision making is not only based on economic decisions alone. The non-economic impulses that form the hedonic treadmill pattern contribute to the behavioral accounting concept which is driven by psychological considerations in decision making.Implications: The implication of this research is a new paradigm in the wider context of accounting theory, especially behavioral accounting where rational and irrational thinking can influence a person's decision making.Novelty: Research tries to see accounting from another perspective to answer social phenomena. By integrating accounting theory and psychology as analytical tool, this research can explain this social phenomenon.